PENGEMBANGAN E-MODUL KIMIA BERORIENTASI LITERASI SAINS PADA MATERI KESETIMBANGAN KIMIA DI SMA NEGERI 3 BENGKULU TENGAH - Ronawati Silaban; Rina Elvia; Febrian Solikhin (University of Bengkulu, 2022)
This study aims to determine the level of feasibility and students responses to the scientific literacy-oriented chemistry e-module on chemical equilibrium material. This research is a development research that uses the ADDIE development model. The ADDIE development model consists of 5 stages, namely; Analysis (analysis), Design (design), Development (development), Implementation (implementation), and Evaluation (evaluation), but in this study is limited to the implementation stage. The sampling technique used purposive sampling, namely class XI MIPA 1 at SMA Negeri 3 Bengkulu Tengah, totaling 29 students. The research data were obtained from media expert validation questionnaires, material expert validation questionnaires, and student responses to the developed e-module. The feasibility level of the e-module based on media expert validation is 94.31% which states that the display in the e-module is feasible from the media aspect, material expert validation is 89.77% which states that the material in the e-module is feasible from the material aspect and science literacy orientation. The response of students to the e-module was 85.73% which stated that the students gave a very positive response to the developed e-module. This shows that the scientific literacy-oriented chemistry e-module on chemical equilibrium material is very suitable for use in the learning process.